Cover Image. Issue 7 (July 2017) - Lahnakoski, Juha M.; Jääskeläinen, Iiro P.; Sams, Mikko; Nummenmaa, Lauri
Abstract : COVER ILLUSTRATION: Multitasking challenges the brain. Lahnakoski and coworkers studied multitasking using a "channel surfing" paradigm where subjects viewed three films either as intact movies one after another, or mixed together in 50‐second segments keeping the storylines intact. Subjects could follow the mixed stories, but the demanding task was reflected in brain activity in the temporal, frontal and occipital cortices, precuneus and cerebellum.